2014
DOI: 10.1093/nar/gku1316
|View full text |Cite
|
Sign up to set email alerts
|

A common set of distinct features that characterize noncoding RNAs across multiple species

Abstract: To find signature features shared by various ncRNA sub-types and characterize novel ncRNAs, we have developed a method, RNAfeature, to investigate >600 sets of genomic and epigenomic data with various evolutionary and biophysical scores. RNAfeature utilizes a fine-tuned intra-species wrapper algorithm that is followed by a novel feature selection strategy across species. It considers long distance effect of certain features (e.g. histone modification at the promoter region). We finally narrow down on 10 inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 39 publications
0
27
0
1
Order By: Relevance
“…To this end, we first analyzed published gene expression data and identified 120 lncRNAs specifically and/or highly expressed in fly testis . To comprehensively identify all lncRNAs expressed in fly, we used a previously developed computational algorithm Gerstein et al 2014;Hu et al 2015) to predict 121 novel intergenic lncRNAs with no overlap with protein-coding genes; the predictions were based on RNA-seq data and RNA structure information ( Fig. 1A; Supplemental Fig.…”
Section: Systematic Identification Of Testis-associated Lncrnas In Drmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we first analyzed published gene expression data and identified 120 lncRNAs specifically and/or highly expressed in fly testis . To comprehensively identify all lncRNAs expressed in fly, we used a previously developed computational algorithm Gerstein et al 2014;Hu et al 2015) to predict 121 novel intergenic lncRNAs with no overlap with protein-coding genes; the predictions were based on RNA-seq data and RNA structure information ( Fig. 1A; Supplemental Fig.…”
Section: Systematic Identification Of Testis-associated Lncrnas In Drmentioning
confidence: 99%
“…We first collected the annotated ncRNAs from FlyBase r5.45 and then adopted a machine learning method to predict novel lncRNAs in Drosophila Gerstein et al 2014;Hu et al 2015). In this method, we used multiple features (e.g., sequence, structure, and expression data) to train a random forest model.…”
Section: Curation Of Known and Novel Lncrnas In Flymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the composed matrix, we applied a balanced random forest (BRF) algorithm (7,27) to train on the annotated coding (mRNAs) and non-coding transcripts (lncRNAs). The predicted probability of being a coding transcript was defined as COME's coding potential score for each given transcript.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, ribosome profiling data suggest that ribosomes may have different binding patterns on mRNAs and lncRNAs (26). Our previous study demonstrated that integration of experiment-based and sequence-derived features could enable classification of ncRNAs from coding sequences with high accuracy (27). However, the model focused only on canonical ncRNAs, and thus, can only predict the local regions of ∼70% of human lncRNAs.…”
Section: Introductionmentioning
confidence: 99%